Self-Assembled Superparamagnetic Iron Oxide Nanoclusters for Universal Cell Labeling and MRI - Chen, Shuzhen (Nanoscale Res Lett, 2016)
Superparamagnetic iron oxide (SPIO) nanoparticles have been widely used in a variety of biomedical applications, especially as contrast agents for magnetic resonance imaging (MRI) and cell labeling. In this study, SPIO nanoparticles were stabilized with amphiphilic low molecular weight polyethylenimine (PEI) in an aqueous phase to form monodispersed nanocomposites with a controlled clustering structure. The iron-based nanoclusters with a size of 115.3 ± 40.23 nm showed excellent performance on cellular uptake and cell labeling in different types of cells, moreover, which could be tracked by MRI with high sensitivity. The SPIO nanoclusters presented negligible cytotoxicity in various types of cells as detected using MTS, LDH, and flow cytometry assays. Significantly, we found that ferritin protein played an essential role in protecting stress from SPIO nanoclusters. Taken together, the self-assembly of SPIO nanoclusters with good magnetic properties provides a safe and efficient method for universal cell labeling with noninvasive MRI monitoring capability. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-016-1479-5) contains supplementary material, which is available to authorized users.